The Ranters Ranting: Reflections on a Ranting Counter Culture - Ellens, G. F. S. (Church history, 1971)
The Ranter counter culture was a phenomenon of Puritan England. It was a movement among lower-class people numbering several thousands—we do not know exactly how many—widely distributed in London and rural England. In describing this phenomenon as a movement, however, one must be cautious since this was not a movement towards a goal: it was a movement of repulsion away from English society as represented by the Puritans. It implied a rejection of the Puritan Establishment—its ethics, its values, and its goals.